2012
DOI: 10.1128/aem.07155-11
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Characterization of a Gradually Inducible Expression Vector for Halobacterium salinarum, Based on the kdp Promoter

Abstract: Gradually inducible expression vectors which are governed by variations of growth conditions are powerful tools for gene expression of conditionally lethal mutants. Furthermore, controlled expression allows monitoring of overproduction of proteins at various stages in their expressing hosts. For Halobacterium salinarum, which is often used as a paradigm for halophilic archaea, such an inducible expression system is not available to date. Here we show that the kdp promoter (Pkdp), which facilitates gene express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…This study also revealed a large number of halophilic archaea in fresh kelp samples. Studies have shown that these microorganisms can counter the hyperosmotic environment outside the cell by adjusting the osmotic pressure inside and outside the cell such that it has a certain tolerance to a high-salt environment [39], potentially even growing normally in a 30% salt concentration [40]. However, it is very difficult for them to adapt to the osmotic pressure in the normal human body.…”
Section: Discussionmentioning
confidence: 99%
“…This study also revealed a large number of halophilic archaea in fresh kelp samples. Studies have shown that these microorganisms can counter the hyperosmotic environment outside the cell by adjusting the osmotic pressure inside and outside the cell such that it has a certain tolerance to a high-salt environment [39], potentially even growing normally in a 30% salt concentration [40]. However, it is very difficult for them to adapt to the osmotic pressure in the normal human body.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, suitable haloarchaeon expression systems are often necessary. Successful homologous expression of haloarchaeal proteins has been reported in halophilic archaeal hosts, such as Halobacterium salinarum ( Nomura and Harada, 1998 ; Kixmüller and Greie, 2012 ; Vauclare et al, 2020 ) and Haloferax volcanii ( Hfx. volcanii ) ( Pohlschroder and Schulze, 2019 ; Haque et al, 2020 ).…”
Section: Mining Of the Red Sea Enzyme Poolmentioning
confidence: 99%
“…To mention only several of the most recent studies, in Hb. salinarum , a gradual inducible gene expression system has been developed (Kixmüller and Greie, 2012 ). It relies on the promoter of the potassium uptake system operon (P kdp ), which responds to potassium cation concentrations in the medium.…”
Section: Halophilesmentioning
confidence: 99%